Evaluating the Effectiveness of the SIGNAL Digital Samsat Application Using the PIECES Framework and Technical Testing - Syakhila, Amanda; Fitria, Rahma; Yulisda, Desvina (Journal of Applied Informatics and Computing, 2025)
The SIGNAL application is a digital service provided by the Indonesian National Police's Traffic Corps (Korlantas Polri) to facilitate online STNK validation. However, several users have reported issues such as unsuccessful verification processes, delays in the delivery of physical documents, slow customer service responses, and login difficulties. This study aims to evaluate the performance of the SIGNAL application using the PIECES framework, which covers six dimensions: Performance, Information, Economic, Control, Efficiency, and Service. Data were collected through questionnaires distributed to 300 users of the SIGNAL application. Each questionnaire indicator was developed based on PIECES theory and statistically tested for validity and reliability using AVE and Composite Reliability. Descriptive and inferential analyses were conducted, including a one-sample t-test to assess user satisfaction. The results show that the average satisfaction score was 3.9 out of 5, with 76% of respondents expressing satisfaction or high satisfaction, 15% neutral, and 9% dissatisfied. The highest satisfaction was recorded in the Economic aspect (mean 4.06), while the lowest was in Control (mean 3.94). Technical testing using Apptim showed the app performed well, with an average response time of 2.4 seconds, CPU usage at 18%, memory usage at 170MB, and no crashes (0% error rate). These findings indicate that SIGNAL is generally effective and stable, though improvements are needed, particularly in service responsiveness and cross-device performance. This research contributes to the theoretical application of the PIECES model in evaluating public digital services and offers insights for improving the quality of e-government systems in Indonesia.